Victorian literature an anthology - Shea, Victor 1960-; Whitla, William 1934- (Chichester, West Sussex, UK Wiley Blackwell, 2015)
"Victorian Literature is a comprehensive and fully annotated anthology with a flexible design that allows teachers and students to pursue traditional or innovative lines of inquiry, from the canon to its extensions to its contexts. Represents the period's major writers of prose, poetry, drama, and more, including Tennyson, Arnold, the Brownings, Carlyle, Ruskin, the Rossettis, Wilde, Eliot, and the Brontës Promotes an ideologically and culturally varied view of Victorian society with the inclusion of women, working-class, colonial, and gay and lesbian writers Incorporates recent scholarship with 5 contextual sections and innovative sub-sections on topics like environmentalism and animal rights; mass literacy and mass media; sex and sexuality; Victorian childhood; melodrama and comedy; the Irish question; ruling India and the Indian Mutiny; innovations in print culture; and the science of race Emphasizes the interdisciplinary nature of the field with a focus on social, cultural, artistic, and historical factors Includes a fully annotated companion website for teachers and students offering expanded context sections, additional readings from key writers, appendices, and an extensive bibliography"--Provided by publisher.
"Victorian Literature is a comprehensive and fully annotated anthology with a flexible design that allows teachers and students to pursue traditional or innovative lines of inquiry"--Provided by publisher.
Includes bibliographical references and index.
Keywords: English literature -- 19th century